1999
DOI: 10.1063/1.478934
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of grafted chain molecules: Influence of head size and chain length

Abstract: Temperature-dependent morphology evolution of the submonolayer clusters grown on fcc metal (110) surfaces J.Morphology and thermochromic phase transition of merocyanine J-aggregate monolayers at the air-water and solid-water interfaces Constant pressure Monte Carlo simulations of a coarse-grained off-lattice model for monolayers of amphiphilic molecules at the air-water interface are presented. Our study focuses on phase transitions within a monolayer rather than on self-aggregation. We thus model the molecule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…At low temperatures, this constraint results in negative surface pressures indicative of the metastability of the system. To alleviate this problem, one should execute simulations in the N⌸T ensemble, as recently considered by Stadler et al ͓5,6͔. Although the majority of the work presented here was performed using the HS model, in which the water subphase was replaced by a hard attractive surface, we have also utilized the ͑9-3͒ potential model to account for surfactantwater interactions. However, using this model, it was found that the monolayer would buckle, akin to the phenomenon termed ''collapse,'' forming bilayer or multilayered structures at temperatures and densities where one would expect to find the liquid phase for a Langmuir monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…At low temperatures, this constraint results in negative surface pressures indicative of the metastability of the system. To alleviate this problem, one should execute simulations in the N⌸T ensemble, as recently considered by Stadler et al ͓5,6͔. Although the majority of the work presented here was performed using the HS model, in which the water subphase was replaced by a hard attractive surface, we have also utilized the ͑9-3͒ potential model to account for surfactantwater interactions. However, using this model, it was found that the monolayer would buckle, akin to the phenomenon termed ''collapse,'' forming bilayer or multilayered structures at temperatures and densities where one would expect to find the liquid phase for a Langmuir monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to reproduce the main features of the generic structure and phase behavior observed experimentally. Here we used the molecular model developed previously in a series of papers by the German group at Mainz [27][28][29][30][31][32][33][34][35]. For completeness, a brief explanation of the molecular potentials is given and their corresponding algebraic expressions are written down.…”
Section: Molecular Model and Simulations Detailsmentioning
confidence: 99%
“…In this paper we present the results of Monte Carlo (MC) simulations of a version of the CGMM's of Langmuir monolayers developed previously [28][29][30][31][32][33][34][35]. In the present model we have incorporated the long-range interactions due to the Coulomb forces among the ionic hydrophilic molecular heads.…”
Section: Introductionmentioning
confidence: 99%
“…The brushes formed by homopolymers were the subjects of many theoretical studies [4][5][6]. Heteropolymeric (amphiphilic) brushes also became recently subjects of simulation studies by means of Monte Carlo [7][8][9][10] and molecular dynamics methods [11][12][13]. Structure and morphology of polymer brush formed by amphiphilic chains were also recently studied by means of Monte Carlo simulations [14].…”
Section: Introductionmentioning
confidence: 99%